2013
DOI: 10.1021/pr301157j
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Herpes Simplex Virus Type 1-Infected Cells Reveals Dynamic Changes of Viral Protein Expression, Ubiquitylation, and Phosphorylation

Abstract: Herpesviruses are among the most complex and widespread human viruses and cause a number of diseases ranging from cold sores to genital infections and encephalitis. While the composition of viral particles has been studied, less is known about the expression of the whole viral proteome in infected cells. Here, we analyzed the proteome of the prototypical Herpes Simplex Virus type 1 (HSV1) in infected cells by mass spectrometry. Using a high sensitivity LTQ-Orbitrap, we achieved a very high level of protein cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Association with membranes is notoriously challenging for MS because of hydrophobicity and limited proteolytic peptides. For comparison, Bell et al also reported the identification of 67 HSV-1 proteins with similar difficulties detecting UL11, UL20, UL49.5, and US5 proteins (18). Overall, our analysis detected ϳ92% of all expected HSV-1 proteins, confirming accurate representation of the viral proteome in our dataset.…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By supporting
confidence: 79%
See 3 more Smart Citations
“…Association with membranes is notoriously challenging for MS because of hydrophobicity and limited proteolytic peptides. For comparison, Bell et al also reported the identification of 67 HSV-1 proteins with similar difficulties detecting UL11, UL20, UL49.5, and US5 proteins (18). Overall, our analysis detected ϳ92% of all expected HSV-1 proteins, confirming accurate representation of the viral proteome in our dataset.…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By supporting
confidence: 79%
“…3G). This prior report also found ICP4 (15 sites) as the most heavily phosphorylated viral protein (18). Interestingly, the overall increase in abundance of phosphorylation events on viral proteins appeared delayed as compared with the respective proteome level (supplemental Fig.…”
Section: Phosphoproteomics Analysis Of Host and Viral Proteome Duringsupporting
confidence: 57%
See 2 more Smart Citations
“…To confirm the specificity of the role of phosphorylation of vdUTPase Ser-187 in viral pathogenesis and replication in mice, we constructed recombinant viruses YK755 (ICP22S5A/S22A/T162A/S167A) and YK757 (UL51T190A), in which the phosphorylation sites in ICP22 and UL51 identified by phosphoproteomic analyses in previous studies (17,43) were replaced with alanines, and their repaired viruses YK756 (ICP22S5A/ S22A/T162A/S167A-repair) and YK758 (UL51T190A-repair) (Fig. 1), and used them to infect cultured cells and mice.…”
Section: Effect Of Phosphorylation Of Vdutpase Ser-187 On Viral Replimentioning
confidence: 98%